IN VITRO ANTI-OBESITY EFFECT OF MACROLICHENS HETERODERMIA LEUCOMELOS AND RAMALINA CELASTRI BY PANCREATIC LIPASE INHIBITORY ASSAY - Shivanna, Rashmi; Parizadeh, Hengameh; Garampalli, Rajkumar H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Obesity is a chronic disorder caused by an imbalance between energy intake and expenditure in which excessive fat will be deposited in adipose tissue and poses a risk to the health and well-being of humans. Agents which inhibit pancreatic lipase play an important role in the treatment of obesity. The aim of this study was to assess the potential effect of macro lichens Heterodermia leucomelos (L.) Poelt a foliose lichen and Ramalina celastri (Sprengel) Krog and Swinscow a fruticose lichen in the treatment of obesity. Methods: In vitro anti-obesity inhibitory effect of macro lichens were evaluated by using chicken pancreatic lipase activity. Lipase was extracted from the chicken pancreas. Different concentrations from 5-25 mg/ml of methanol and ethyl acetate extracts of lichens Heterodermia leucomelos and Ramalina celastri was incubated with pancreas lipase. Results: With the increase in the concentration of extracts the higher inhibition of the enzyme was observed. Solvent methanol showed good activity compared to ethyl acetate. Percentage of inhibition ranged from 19.7-69.8 and 20.0-86.6 % in the methanol extract of Heterodermia leucomelos and Ramalina celastri respectively. Comparatively lichen Ramalina celastri in methanol extract showed maximum inhibition of 86.6 %, whereas ethyl acetate showed an inhibition of 63.0% at 25 mg/ml against enzyme lipase. Conclusion: In the present study, the inhibitory activity of lichen indicates its protective role in treating obesity. Molecular sequencing of this lichen helps in future to determine the various metabolic pathways that are responsible for the production of novel compounds.